Gamification of Educational Technology: a Narrative Review - Aldiansyah, Muhamad; Amril Jaharadak, Adam; ., . (International Journal of Engineering and Technology, 2018)
Student motivation and engagement are major problems in education. Gamification is one way to increase student motivation and engagement by combining game element in the educational environment. There are some empirical researches and review paper that has been conducted to give an evidence of gamification positive effect for educational technology but review papers that discuss practical suggestion have rarely been studied. This review is focused on papers that give an empirical evidence for gamification on learning in the context of narrative analysis to proposed best practices to do this research field. The study of gamification in educational technology is the basis this narrative literature review was made. Terms of search used is gamification, learning, student, engagement, motivation, and education. Gamification on e-learning that has no purpose on student motivation and engagement were excluded from the search terms. Fifteen papers were selected for review as they are relevant to the criteria. This review indicates that the use of game element has a positive influence on educational technology for the student, even there are various combinations for the chosen of learning activity, subject, game elements, method, sample size, and duration.
Keywords: gamification; education; technology; learning; student; engagement; motivation